Peran Kantor Urusan Agama dalam Implementasi Sighat Taklik Talak untuk Perlindungan Rumah Tangga di Kec. Medan Petisah - Muannas; Artika; Della Patika Sari; Dewi Sartika; Indri Apriliani; Salahuddin Harahap (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Sighat taklik talak is one of the essential aspects of marriage that aims to provide protection for both husband and wife in anticipating potential violations of rights within the household. This study aims to explore the role of the Office of Religious Affairs (KUA) of Medan Petisah, Medan City, in implementing sighat taklik talak as an instrument for household protection. This research employed a qualitative approach with data collection techniques including interviews, observations, and document studies. The findings indicate that KUA Medan Petisah plays a strategic role in educating and guiding prospective spouses on the importance of sighat taklik talak. This role is carried out through two main efforts: first, direct socialization with prospective couples regarding the meaning and urgency of sighat taklik talak as a form of legal and moral protection in marriage; and second, the organization of premarital courses that equip couples with in-depth understanding of the rights and responsibilities of husbands and wives, including the position of taklik talak in Islamic law and its role in preventing marital disharmony. Thus, this paper asserts that the existence and active role of KUA in implementing sighat taklik talak contributes significantly to strengthening family resilience in Medan City